Radio and gamma-ray properties of extragalactic jets from the TANAMI sample - Boeck, M.; Kadler, Matthias; Müller, Cornelia; Tosti, G.; Ojha, R.; Wilms, Jörn; Bastieri, D.; Burnett, T.; Carpenter, B.; Cavazzuti, E.; Dutka, M.; Blanchard, J.; et al. (Astronomy & Astrophysics, 2016)
The TANAMI program has been observing parsec-scale radio jets of southern (declination south of - 30°) γ-ray bright AGN, simultaneously with Fermi/LAT monitoring of their γ-ray emission, via high-resolution radio imaging with Very Long Baseline Interferometry techniques. We present the radio and γ-rayproperties of the TANAMI sources based on one year of contemporaneous TANAMI and Fermi/LAT data. A large fraction (72%) of the TANAMI sample can be associated with bright γ-ray sources for this time range. Association rates differ for different optical classes with all BL Lacs, 76% of quasars, and just 17% of galaxies detected by the LAT. Upper limits were established on the γ-ray flux from TANAMI sources not detected by LAT. This analysis led to the identification of three new Fermi sources whose detection was later confirmed. The γ-ray and radio luminosities are related by L ∞ L . The brightness temperatures of the radio cores increase with the average γ-ray luminosity and the presence of brightness temperatures above the inverse Compton limit implies strong Doppler boosting in those sources. The undetected sources have lower γ/radio luminosity ratios and lower contemporaneous brightness temperatures. Unless the Fermi/LAT-undetected blazars are much γ-ray-fainter than the Fermi/LAT-detected sources, their γ-ray luminosity should not be significantly lower than the upper limits calculated here.
Keywords: Galaxies: active; Galaxies: jets; Galaxies: nuclei; Gamma rays: galaxies; Radio continuum: galaxies